2009
DOI: 10.1038/modpathol.2009.57
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer of transition zone origin lacks TMPRSS2–ERG gene fusion

Abstract: Recent studies have shown a unique chromosomal rearrangement that leads to the fusion of 5 0 -transmembrane protein serine proteinase-2 (TMPRSS2) with the EST-related gene (ERG) in prostate cancer. In this study, we used fluorescence in situ hybridization to evaluate TMPRSS2-ERG gene fusion in prostate cancer of different zonal origins. Radical prostatectomy specimens with multifocal prostate cancer were obtained from 30 patients who were treated at our institution. Two separate tumor foci in each specimen, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
54
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 24 publications
(40 reference statements)
7
54
2
Order By: Relevance
“…Similar to Demichelis et al 5 and in contrast to Guo et al, 24 we detected TMPRSS2-ERG gene fusion in 7 (12%) informative transition zone tumors. Of the fusion-positive transition zone prostate cancers, two were Gleason score 6 and five were Gleason score 7; two involved extraprostatic tissue, four were organ confined, and in one case the tumor involved the surgical margin of resection.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to Demichelis et al 5 and in contrast to Guo et al, 24 we detected TMPRSS2-ERG gene fusion in 7 (12%) informative transition zone tumors. Of the fusion-positive transition zone prostate cancers, two were Gleason score 6 and five were Gleason score 7; two involved extraprostatic tissue, four were organ confined, and in one case the tumor involved the surgical margin of resection.…”
Section: Discussionsupporting
confidence: 90%
“…This frequency of TMPRSS2-ERG fusion is similar to the value of 30% (134 of 445) found by Attard et al, 8 but lower than the value of 49% (58 of 118) found by Perner et al 2 and 43% (13 of 30) found by Guo et al, 24 who also assessed ERG gene alterations using a FISH breakapart assay. As the incidence of ERG gene alterations have been linked to clinical stage and Gleason score, these differences may be explained, at least in part, by the distinct clinical compositions of the prostate tumor sets surveyed in each study, as suggested by Attard et al 8 Among our positive cases, deletion, rather than translocation, was found to be the main mechanism for TMPRSS2-ERG gene fusion in both transition zone prostate cancers (57%) and peripheral zone prostate cancers (58%), as previously reported in other studies.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations